Determinants of FDI: Does Democracy Matter? - Farazmand , Hasan; Moradi , Mahvash (Journal of Law and Governance, 2014)
Having access to foreign investments allows a country to take advantage of opportunities to which they would otherwise not have access. Many factors interfere with the ability to attract investments in developing countries, but there is lack of consensus on which factors play an unambiguous role. Using different econometric techniques for a data sample of 5 developing countries and the period 1990 to 2012, this study identifies those factors that most explain the determinants of foreign direct investment. Based on results, democracy can positively affect investors’ decisions about where to locate capital. The findings also show that foreign direct investment as a share of GDP, is significantly associated with low corruption, inflation, high openness, literacy rate and infrastructure.